2016
DOI: 10.1186/s13098-016-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

CML/RAGE signal induces calcification cascade in diabetes

Abstract: ObjectiveVascular calcification is a significant predictor of coronary heart disease events, stroke, and lower-limb amputation. Advanced glycation end-products (AGEs) play a key role in the development of vascular calcification. However, the role of Nε-carboxymethyl-lysine (CML), a major active ingredient of heterogeneous AGEs, in the development of atherosclerotic calcification in diabetic patients and the underlying mechanism remain unclear. Hence, the role and the mechanism of CML in the transmission pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Our previous study found that Ne-carboxymethyl-lysine (CML), a key component of serum AGEs, can be seen as an early indicator for the calcification of anterior tibial artery plaque in patients with diabetic amputation [29]. Further, our research group successfully replicated the animal and cell model of calcification in diabetic plaque using CML [30], finding that the calcification of the anterior tibial artery plaque in patients with diabetic foot amputation showed the appearance of focal microcalcification [31]. In addition, our research group previously synthesised the CML fluorine-18 ( 18 F)-labelled tracer, and carried out a pharmacokinetic study of the novel molecular probe under physiological and pathological conditions [32].…”
Section: Role Of Advanced Glycation End Products In the Formation Of mentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study found that Ne-carboxymethyl-lysine (CML), a key component of serum AGEs, can be seen as an early indicator for the calcification of anterior tibial artery plaque in patients with diabetic amputation [29]. Further, our research group successfully replicated the animal and cell model of calcification in diabetic plaque using CML [30], finding that the calcification of the anterior tibial artery plaque in patients with diabetic foot amputation showed the appearance of focal microcalcification [31]. In addition, our research group previously synthesised the CML fluorine-18 ( 18 F)-labelled tracer, and carried out a pharmacokinetic study of the novel molecular probe under physiological and pathological conditions [32].…”
Section: Role Of Advanced Glycation End Products In the Formation Of mentioning
confidence: 99%
“…It is known that AGEs have two major receptors in atherosclerotic plaque: receptor for advanced glycation end products (RAGE) and galectin-3 (Gal-3) [27,31,37,38]. Mainly distributed in microcalcifications and unstable plaques caused by inflammation, RAGE, a membrane receptor with a transmembrane domain, is mostly found in inflammatory infiltrating mononuclear macrophages and SMCs [39].…”
Section: Role Of Advanced Glycosylation End Product Receptors In Matrmentioning
confidence: 99%
See 2 more Smart Citations
“…Although evidence concerning the effects of fructose-derived AGEs remains limited, it has recently been posited that they may exacerbate hepatic lipogenesis via inactivation of hepatic adenosine monophosphate-activated protein kinase [48]. A thorough discussion of the effects of MG and fructose-derived AGEs is beyond the scope of the current review, however, and readers are referred to several recent articles on the effects and potential mechanisms of AGEs [47,49,50,51,52]. …”
Section: Fructose and Intestinal De Novo Lipogenesis (Dnl)mentioning
confidence: 99%